IDENTIFICATION OF COLLETOTRICHUM GLOEOSPORIOIDES, EXSEROHILUM ROSTRATUM AND GLIOCLADIUM VERMOESENI ASSOCIATED WITH LEAF ROT DISEASE OF COCONUT IN INDIA - N. Srinivasan; M. Gunasakeran (International Coconut Community, 1994)
Leaf rot is a common disease predominantly superimposed on root (wilt) affected coconut palms in India. Three fungi implicated in the disease have been found to be Colletotrichum gloeosporioides, Exserohilum Yostratum and Gliocladium vermoeseni. The cultural characters and morphological features of these fungi have been deBcribed. The pathogenic role of these fungi has been confirmed. The three fungi independently induced symptoms leading to leaf rot. E. rostratum developed the disease symptom relatively faster. Pin prick injury in leaf pieces generally favoured the fungi in infection and had pronounced effect for G. vermoeseni.